Tradução, adaptação transcultural e validação de face da assistance to participate scale para a população brasileira - Alice Wilken de Pinho (2023)
Introduction: It's important for healthcare professionals as well as families of children and adolescents with disabilities to have assessment tools that encompass participation as an outcome, primarily for parents' assistance with games and fun activities at home and in the community. The Assistance to Participate Scale (APS) was developed in english and has been utilized in clinical practices and scientific research. Objective: To translate and cross-culturally adapt the APS into Brazilian portuguese. Method: It was done in six stages for the translation and equivalences tests of the instrument. 1) Translation phase was done with 2 bilingual translators (portuguese-english), with and without knowledge of the instrument. 2) Summary of translations conducted by the researches 3) Back translation by 2 bilingual translators english-portuguese. 4) Expert committee, consisting of 5 occupational therapists experienced in the assessments and intervention processes of the ‘participation’ and knowledgeable in methodological processes for cross-cultural adaptation. 5) Cognitive interview with 12 caregivers of children and/or adolescents with disabilities. 6) Submission for author. Results and Discussion: In the translation and back-translation stages, over 80% of the translated sentences achieved both idiomatic and conceptual equivalences. The Expert Committee approved 61,90% of the translated sentences, with discrepancies being resolved after analyzing the recommendations. During the Cognitive Interview stage, the participants reported difficulties in understanding certain sentences categorized by the Question Assessment System under reading, instructions and clarity, which were resolved through four rounds of interviews. Conclusion: The second pre-final version of the APS, translated and culturally adapted for Brazilian Portuguese, has been made available.